The effect of training and development opportunities and physical workplace conditions on job satisfaction “an application in telecommunication sector” - Alim, Özgür (My University, 2002)
The objective of this study is to find out the effects of ‘training and development opportunities’ and ‘physical workplace conditions’ on the job satisfaction level of the employees working in telecommunication sector in Turkey. This study also investigates the factors of job satisfaction, to which employees attach the most importance. Besides it makes a comparison of the job satisfaction of private and public sector employees and finds out the overall job satisfaction of the employees working in telecommunication sector in Turkey. This research is conducted with the help of a questionnaire, which is prepared by considering the several factors of job satisfaction. These factors are; training and development opportunities, physical workplace conditions, work itself, management, company and administrative policies, social activities, salary and rewards, communication, and co-workers. The population of the study is selected by convenience sampling from six private sector companies and Turk Telekom. These private sector companies are the biggest telecommunication companies and Turk Telecom is the only public sector company in telecommunication in Turkey. While calculating the job satisfaction, equal amount of employees are chosen from the public and private sector in order to compare each other and to avoid errors, which can occur according to the workplace position of the employees. At the end of the study, we have found out that employees, working in telecommunication sector, are generaly satisfied with their job in Turkey. Although private sector employees were more satisfied with their job, we could not find significant difference between the job satisfaction levels of private and public sector employees. Besides we have found out that ‘training and development opportunities’ and ‘physical workplace conditions’ have a big effect on the job satisfaction of the employees. In addition to these we have found out that the most important factor is ‘salary and rewards’,and the least important factor is ‘social activities’ for the employees working in telecommunication sector in Turkey.
Keywords: Ekonomik Gelişim; Genel yönetim; İletişim; Yürütmenin yönetimi